2023
DOI: 10.3390/nu15122767
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergens in Ultra-Processed Foods According to the NOVA Classification System: A Greek Branded Food Level Analysis

Abstract: Ultra-processed foods’ (UPFs’) consumption has been positively linked to the presence of allergic symptoms, but it is yet unknown whether this is linked to their nutritional composition or allergen load. This study used the ingredient lists available in the Greek Branded Food Composition Database, HelTH, to classify foods (n = 4587) into four grades of food processing (NOVA1–4) according to the NOVA System. Associations between NOVA grades and the presence of allergens (as an ingredient or trace) were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The AAP recommends that sugar sweetened drinks, the addition of salt to foods, or the consumption of nutrient-poor discretionary foods with high levels of saturated fat, added sugars, and/or added salt should not be included during the transition to solid foods [ 104 ]. UPFs have been linked to allergic conditions such as asthma, eczema, and wheezing [ 119 , 120 ]. It has been hypothesized that UPFs can contribute to food allergy development, either due to their poor nutritional composition or as a result of higher levels of food processing [ 119 ].…”
Section: Dietary Factors In Allergic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The AAP recommends that sugar sweetened drinks, the addition of salt to foods, or the consumption of nutrient-poor discretionary foods with high levels of saturated fat, added sugars, and/or added salt should not be included during the transition to solid foods [ 104 ]. UPFs have been linked to allergic conditions such as asthma, eczema, and wheezing [ 119 , 120 ]. It has been hypothesized that UPFs can contribute to food allergy development, either due to their poor nutritional composition or as a result of higher levels of food processing [ 119 ].…”
Section: Dietary Factors In Allergic Diseasementioning
confidence: 99%
“…UPFs have been linked to allergic conditions such as asthma, eczema, and wheezing [ 119 , 120 ]. It has been hypothesized that UPFs can contribute to food allergy development, either due to their poor nutritional composition or as a result of higher levels of food processing [ 119 ]. In addition, the low pH of infant foods, particularly infant pouches, has led to concerns regarding an increase in food allergy [ 121 ].…”
Section: Dietary Factors In Allergic Diseasementioning
confidence: 99%
“…Several studies have found a positive association between the consumption of UPFs and allergic symptoms in children and adolescents [141][142][143][144]. Katidi et al suggested that UPFs may lead to a higher exposure to additives and allergens, which may contribute to the allergy process [145]. This may be due to the higher content of allergens in UPFs compared to lessprocessed foods [146].…”
Section: Allergiesmentioning
confidence: 99%
“…Moreover, individuals with food allergies may develop sensitization to other foods that contain homologous proteins [147]. Therefore, individuals affected by multiple food allergies should be cautious about consuming UPFs [145]. There is increasing evidence that the gut dysbiosis is related to the development of a food allergy, although this specific pathogenesis is still unknown [142,148].…”
Section: Allergiesmentioning
confidence: 99%
See 1 more Smart Citation